Sie sind auf Seite 1von 47

4

The Laplace Transform

Exercises 4.1

1.

2.

3.

4.

5.

6.

7.

8.

9.

10.

Transform Exercises 4.1 1. 2. 3. 4. 5. 6. 7. 8. 9. 10. { f (

{f (t)} = 1 e st dt + e st dt = 1

s

0

1

=

1 s e s 1 s 0 1 s e s = 2

s

e st

e s

1

0

1

s

1

s ,

e st

1

s> 0

− s − 1 0 − 1 s 1 s , e − st ∞ 1

{f (t)} = 2 4e st dt = 4

s

0

e st

2

=

0

4 (e 2s 1),

s

s> 0

st 2 = 0 − 4 ( e − 2 s − 1) , s s>

{f (t)} = 1 te st dt + e st dt = 1 s te st 1

0

1

s

2

e st

1

0

1

s

e st

1

=

1

s

e s

1 2 e s 0 1 2 1 s (0 e s ) =

s

s

1 2 (1 e s ),

s

s> 0

{f ( t ) } = 1 (2 t + 1) e − s t f (t)} = 1 (2t + 1)e st dt = 2

s

0

te st 2 2 e st 1 s e st

s

1

0

=

2

s

e s

2 2 e s 1

s

s e s 0

2 2 1

s

s = 1

s (1 3e s ) + 2 2 (1 e s ),

s

s> 0

s ) + 2 2 (1 − e − s ) , s s> 0 {

{f (t)} = π (sin t)e st dt = s + 1 e st sin t

0

s

2

1 + 1 e st cos t

s

2

= 0 +

1

+ 1 e πs 0

s

2

s 2 + 1 =

1

1 + 1 (e πs + 1),

s

2

π

0

s> 0

{f (t)} = π/2 (cos t)e st dt = s + 1 e st cos t +

=

0,

t,

0 0 +

0 <t< 1

t > 1

s

2

1 + 1 e πs/2 =

s 2

s

1 + 1 e πs/2 ,

s 2

2

+ 1 e st sin t

1

e − πs/ 2 , s 2 2 + 1 e − s t sin t

s> 0

f (t) =

+ 1 e − s t sin t 1 s > 0 f ( t )

{f(t)} = te st dt = 1

s

1

te st 1

s

2

e st

1

= 1 s e s +

1 2 e s ,

s

π/2

s > 0

f (t) = 0, 2t 2,

0 <t< 1

t> 1

0 , 2 t − 2 , 0 < t < 1 t> 1 { f

{f(t)} = 2 (t 1)e st dt

1

=

2 1 s (t 1)e st 1

s

2

e st

1

=

2 2 e s ,

s

s > 0

f (t) =

1 t,

0,

0 <t< 1 t> 0

0 f ( t ) = 1 − t, 0 , 0 <t< 1 t> 0

{f(t)} = 1 (1 t)e st dt = 1 s (1 t)e st +

0

1

s 2

e st

1

=

0

f (t) =

0,

c,

0,

0 <t<a

a < t < b ;

t>b

c,  0 , 0 <t<a a < t < b ; t>b { f (

{f(t)} =

a

b

ce st dt = c

s

e st

1

2 e s +

s

1

s

1

s 2 ,

s > 0

b

= c (e sa e sb ), s > 0

a s

165

Exercises 4.1

11.

12.

13.

14.

15.

16.

17.

18.

19.

21.

23.

25.

Exercises 4.1 11. 12. 13. 14. 15. 16. 17. 18. 19. 21. 23. 25. { f

{f (t)} =

0

e t+7 e st dt = e 7 e (1s)t dt =

0

e 7

1 s

e (1s)t

= 0

0

e

7

1 s =

e

7

s 1 ,

s> 1

{f ( t ) } = ∞ f (t)} =

0

e 2t5 e st dt = e 5 e (s+2)t dt =

0

e 5

s +

2 e (s+2)t

e 5

0

= s + 2 ,

s> 2

t ∞ e − 5 0 = s + 2 , s> − 2 { f

{f (t)} = te 4t e st dt =

0

0

te (4s)t dt =

1

4 s

te (4s)t

1 s) 2 e (4s)t

(4

=

1 s) 2 ,

0 (4

(4 − s ) t (4 − ∞ = 1 s ) 2 , 0 (4

{f (t)} =

0

t 2 e 2t e st dt = t 2 e (s+2)t dt

0

 

=

{f ( t ) } f (t)}

=

=

=

{f ( t ) } f (t)}

=

=

=

1

+ 2 t 2 e (s+2)t

s

2 2) 2 te (s+2)t

(s +

2 2) 3 e (s+2)t

(s +

e t (sin t)e st dt = (sin t)e (s+1)t dt

0

0

(s + 1)

+ 1 e (s+1)t sin t

(s + 1) 2

1

1

(s + 1) 2 + 1 = s 2 + 2s + 2 ,

(s + 1) 2 + 1 e (s+1)t cos t

1

s> 1

0

e t (cos

t)e st dt = (cos t)e (1s)t dt

0

1 s

+ 1 e (1s)t cos t +

(1

s) 2

(1 s) 2 + 1 e (1s)t sin t

1

1 s

s 1

(1 s) 2 + 1 = s 2 2s + 2 ,

s> 1

0

0

0

=

2

(s + 2) 3 ,

s> 2

{f ( t ) } = ∞ t (cos t ) e − s t f (t)} = t(cos t)e st dt

0

=

st s 2 + 1

s 2 1

(s 2 + 1) 2

s 2 1

= s> 0

(s 2 + 1) 2 ,

(cos t)e st +

t

2s

1) 2 (sin t)e st

(s 2 +

s 2 + 1 +

0

{f ( t ) } = ∞ t (sin t ) e − s t f (t)} = t(sin t)e st dt

0

=

t

2s

s 2 + 1

(s 2 + 1) 2

2s

= s>

(s 2 + 1) 2 ,

0

(cos t)e st

st s 2 + 1 +

s 2 1

1) 2 (sin t)e st

(s 2 +

0

s> 4

2 (sin t ) e − s t ( s 2 + ∞ 0 s> 4

2 (sin t ) e − s t ( s 2 + ∞ 0 s> 4

2 (sin t ) e − s t ( s 2 + ∞ 0 s> 4

2 (sin t ) e − s t ( s 2 + ∞ 0 s> 4

{2t 4 } = 2 4! 5

s

{4t 10} =

4

2 10

s

s

{t 2 + 6t 3} =

2

3 + 6 2 3

s

s

s

{t 3 + 3t 2 + 3t + 1} = 3! 4 + 3

s

2

3

1

s 3 + s 2 +

s

20.

22.

24.

26.

4 + 3 s 2 3 1 s 3 + s 2 + s 20. 22.

4 + 3 s 2 3 1 s 3 + s 2 + s 20. 22.

4 + 3 s 2 3 1 s 3 + s 2 + s 20. 22.

4 + 3 s 2 3 1 s 3 + s 2 + s 20. 22.

{t 5 } = 5!

s

6

{7t + 3} =

7

2 + 3

s

s

{−4t 2 + 16t + 9} = 4 2 3 + 16

s

s

2

+ 9

s

{8t 3 12t 2 + 6t 1} = 8 3! 4 12 2 3 + 6 2 1

s

s

s

s

166

Exercises 4.1

27.

29.

31.

Exercises 4.1 27. 29. 31. { 1 + e 4 t } = 1 s +

Exercises 4.1 27. 29. 31. { 1 + e 4 t } = 1 s +

Exercises 4.1 27. 29. 31. { 1 + e 4 t } = 1 s +

{1 + e 4t } =

1

s + s 4

1

{1+2e 2t + e 4t } =

1

s + s 2 + s 4

2

1

{4t 2 5 sin 3t} = 4 s 3 5 s 2 + 9

2

3

28.

30.

32.

s 3 − 5 s 2 + 9 2 3 2 8 . 3 0 .

s 3 − 5 s 2 + 9 2 3 2 8 . 3 0 .

s 3 − 5 s 2 + 9 2 3 2 8 . 3 0 .

{t 2 e 9t + 5} =

{e 2t 2 + e 2t } =

{cos 5t + sin 2t} =

2

s + 9 + 5

s

1

s 3

s 2 2

1

1

s + s + 2

s

2

+

s 2 + 25

s 2 + 4

33.

35.

36.

37.

+ s + 2 s 2 + s 2 + 25 s 2 + 4 33.

{sinh kt} =

{e t sinh t } = e t sinh t} =

k

s 2 k 2

{ sinh kt } = { e t sinh t } = k s 2 −

e t e t e t

2

=

k s 2 − k 2 e t e t − e − t 2 =

{e − t cosh t } = e t cosh t} =

e t − e − t 2 = { e − t cosh t } =

e t e t + e t =

2

34.

t } = e − t e t + e − t = 2 34. {

{cosh kt} =

1 2 e 2t 1 2 =

1 1

2(s 2)

2s

1 2 + 1 2 e − 2 t = 1 2 + 1 2 e 2t =

1 1

2s + 2(s + 2)

{sin 2 t cos 2 t } = sin 2t cos 2t} =

2 t = 1 1 2 s + 2( s + 2) { sin 2 t

2 sin 4t =

1

2

s 2 + 16

38.

{cos 2 t } = cos 2 t} =

= 2 sin 4 t = 1 2 s 2 + 16 38. { cos 2

1 2 + 1 2 cos 2t =

1 1

s

2s + 2 s 2 + 4

39. (a)

Using integration byparts for α > 0,

s s 2 k 2

Γ(α + 1) = t α e t dt = t α e t

0

0

+ α t α1 e t dt = αΓ(α).

0

(b)

Let u = st so that du = s dt. Then

Γ( α ) . 0 (b) Let u = st so that du = s dt

{t α } = e st t α dt =

0

0

e u u

s

α 1 s du =

1

s α+1 Γ(α + 1),

α> 1.

40. (a)

{t 1/2 } = Γ(1/2) = π { t − 1 / 2 } = Γ ( 1 / 2 ) = π

s

s

1/2

41.

(b)

(c)

{ t 1 / 2 } {t 1/2 }

=

Γ(3/2)

π

=

s

3/2

2s 3/2

{t 3/2 } = Γ(5/2) = 3 π { t 3 / 2 } = Γ ( 5 / 2 ) = 3 √

s

5/2

4s 5/2

Identifying f (t) = t n we have f (t) = nt n1 , n = 1, 2, 3,

Then, since f (0) = 0,

42.

For n = 1,

For n = 2,

For n = 3,

n

n { t n − 1 } =

{t n1 } =

n { t n − 1 } =

{t} = 1 s

{1 } = 1} =

{ t } = 1 s { 1 } = { t 2 } = 2

{t 2 } t 2 }

= 2

{ t } = 1 s { 1 } = { t 2 } = 2

{t} =

1

s 2 .

2

s

s 3 .

{t 3 } = 3 t 3 } = 3

s

{ t 3 } = 3 s { t 2 } =

{t 2 } =

 

6

s 4 .

{nt n1 } = s

} =   6 s 4 . { nt n − 1 } = s {

{t n }

and

6 s 4 . { nt n − 1 } = s { t n }

{t n } = n

s

nt n − 1 } = s { t n } and { t n }

{t n1 }.

Let F (t) = t 1/3 . Then F (t) is of exponential order, but f (t) = F (t) = 3 t 2/3 is unbounded near t = 0 and

hence is not of exponential order.

1

167

Exercises 4.1

Let f (t)=2te t 2 cos e t 2 =

transform exists. Using integration byparts we have

d

dt sin e t 2 . This function is not of exponential order, but we can show that its Laplace

not of exponential order, but we can show that its Laplace { 2 te t 2

{2te t 2 cos e t 2 } =

0

e st

dt sin e t 2 dt =

d

= s e st sin e t 2 dt = s

0

d = s ∞ e − s t sin e t 2 dt = s 0

a lim e st sin e t 2

{sin e t 2 }.

a

0

+

s a e st sin e t 2 dt

0

Since sin e t 2 is continuous and of exponential order,

sin e t 2 is continuous and of exponential order, { sin e t 2 }

{sin e t 2 } exists, and therefore

{2 te t 2 cos e t 2 } exists. 2te t 2 cos e t 2 } exists.

43. The relation will be valid when s is greater than the maximum of c 1 and c 2 .

44. Since e t is an increasing function and t 2 > ln M + ct for M > 0 we have e t 2 > e ln M +ct = Me ct for t sufficiently

large and for any c. Thus, e t 2 is not of exponential order.

45. Bypart (c) of Theorem 4.1

{ e ( a + ib ) t } = {e (a+ib)t } =

 

1

1

(s a) + ib

s a + ib

s

(a + ib) =

(s a) ib (s a) +

ib =

(s a) 2 + b 2 .

ByEuler’s formula, e iθ = cos θ + i sin θ, so

formula, e i θ = cos θ + i sin θ , so { e (

{e (a+ib)t }

=

=

=

{e a t e i b t } e at e ibt }

( a + i b ) t } = = = { e a t e

{e at (cos bt + i sin bt)}

e i b t } { e a t (cos bt + i sin bt )

{e at cos bt} + i

(cos bt + i sin bt ) } { e a t cos bt } +

{e at sin bt}

s a

b

(s a) 2 + b 2 + i (s a) 2 + b 2 .

Equating real and imaginaryparts we get

) 2 + b 2 . Equating real and imaginaryparts we get { e a t

{e at cos bt}

=

s a + b 2 (s a) 2

and

bt } = s − a + b 2 ( s − a ) 2 and

{e at sin bt} =

b

(s a) 2 + b 2 .

46. We want f (αx + βy ) = αf (x) + βf (y ) or

m(αx + βy) + b = α(mx + b) + β(my + b) = m(αx + βy)+(α + β)b

for all real numbers α and β. Taking α = β = 1 we see that b = 2b, so b = 0. Thus, f (x) = mx + b will be a

linear transformation when b = 0.

Exercises 4.2


1.


2.

3. 1 2 48

1 s 3 = 1 2

1 s 4 = 1 6

s

s 3 = 1 2 t 2 s 3 = 1 2 t 2

2

s

5

s 4 = 1 6 t 3 s 4 = 1 6 t 3

3!

=

= 1 2 t 2 2 s 5 s 4 = 1 6 t 3 3!

1 2 48 · 4!

s

24

s

4 · 1

2 4

5 = t 2t 4

3!

1

4. 2 1 3 2 =

s

s

=

=

− 2 t 4 3! 1 4. 2 − 1 3 2 = s s =

6 = 4t 2 3 t 3 +

· 5!

s

1

120 t 5

s

6 · s 4 + 120

5. (s + 1) 3

s

4

1 2 1 · 3! + 3 · 1 4 =1+3t + 3 t 2
1
2
1 · 3!
+ 3 · 1
4 =1+3t + 3 t 2 +
2 + 3
s
s
2 · s 3 + 6
s
2
1 s + 4 · 1 2 + 2 · 2 3 =1+4t + 2t 2
s
s

1

6 t 3

6. (s + 2) 2

s

3

168

Exercises 4.2

7.

8.

9.

10.

11.

12.

13.

14.

15.

16.

17.

18.

19.

20.

21.

22.

23.

24.

25.

12. 13. 14. 1 5 . 16. 17. 18. 19. 20. 21. 22. 23. 24. 25.

s 2 1

1

s

2 = t 1 + e 2t

1

s +

s + s 5 − + s 5

s

4

6

+ 8 =

1

1 + e 2 t 1 s + s + s 5 − s 4 6

4 · s + 4 · s 5

1

1

4!

s + 8 =4+ 1 4 t 4 e 8t

1

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

s + 8 =4+ 1 4 t 4 − e − 8 t 1 4 s

4s + 1 =

1

5s 2 =

1

4 − e − 8 t 1 4 s + 1 = 1 5 s −

4 − e − 8 t 1 4 s + 1 = 1 5 s −

s + 1/4 =

1

1

·

4

1

1

4 e t/4

5 e 2t/5

· s 2/5 = 1

1

5

s 2 + 49 =

5

2 t/ 5 · s − 2 / 5 = 1 1 5 s 2 +

5 7 ·

s 2 + 49 = 5 7 sin 7t

7

10s

16 = 10 cos 4t

s 2 +

4s

1 =

4s 2 +

10 s 1 6 = 10 cos 4 t s 2 + 4 s 1 =

1

1 =

4s 2 +

4 t s 2 + 4 s 1 = 4 s 2 + 1 1 =

1/4 = cos

s 2 + 1/4 =

1/2

s

s 2 +

1

·

2

1

2

1

2

t

sin

1

2 t

+ 1 / 4 = 1 / 2 s s 2 + 1 · 2 1

+ 1 / 4 = 1 / 2 s s 2 + 1 · 2 1

2s 6

+ 9

=

s 2

s + 1 s 2 + 2 =

t sin 1 2 t 2 s − 6 + 9 = s 2 s +

t sin 1 2 t 2 s − 6 + 9 = s 2 s +

2 ·

s

3 + 9 = 2 cos 3t 2 sin 3t

2

2

s 2 + 2

s 2 + 9 2 · s 2

s

1

= cos 2t + 2 sin 2 t

2

s 2 + 2 +

√ 2 t + √ 2 sin √ 2 t 2 s 2 + 2 +

√ 2 t + √ 2 sin √ 2 t 2 s 2 + 2 +

√ 2 t + √ 2 sin √ 2 t 2 s 2 + 2 +

√ 2 t + √ 2 sin √ 2 t 2 s 2 + 2 +

√ 2 t + √ 2 sin √ 2 t 2 s 2 + 2 +

s 2 + 3s =

s + 1 s 2 4s =

1

3 · s − 3 · s + 3 = 1 3 − 1 3 3 · s 3 · s + 3 = 1 3 1 3 e 3t

1

1

1

1

· s + 3 = 1 3 − 1 3 e − 3 t 1 1

1 4

·

1

s + 4 · s 4 = 1 4 + 5 4 e 4t

5

1

s 2 + 2s 3 =

s

s 2 + s 20 =

1

1 s 2 + 2 s − 3 = s s 2 + s − 20

1 s 2 + 2 s − 3 = s s 2 + s − 20

0.9s

0.2) =

(s 0.1)(s

+

1

4 · s 1 + 4 · s + 3 = 1

1

9 e 4t 9 · s 4 9 · s + 5 = 1

1

3

1

4 e t +

1

1

1

3

4 e 3t

1

9 e 5t

1 3 1 4 e t + 1 1 1 3 4 e − 3 t

(0.3) ·

s 1 0.1 + (0.6) ·

1

0.2 = 0.3e 0.1t + 0.6e 0.2t

s +

√ 3 )( s + √ 3) = 3 )(s + 3) =

e − 0 . 2 t s + − √ 3 )( s + √ 3)

s 3

0 . 2 t s + − √ 3 )( s + √ 3) = s
0 . 2 t s + − √ 3 )( s + √ 3) = s

(s

(s

2)(s 3)(s 6) =

s

√ 3
√ 3

s 2

3 = cosh 3 t 3 sinh 3 t

s

s 2 3 3 ·

2 ·

1

1

1

1

 

s 2 s 3 + 2 ·

s 6 = 1 2 e 2t e 3t + 1 2 e 6t

1

s( s − 1)( s + 1)( s − 2) = (s 1)(s + 1)(s 2) =

s

+

1

2

e 6 t 1 s ( s − 1)( s + 1)( s − 2) =

1

2 ·

1

1

1

s s 1 3 · s + 1 + 6 · s 2

1

1

1

5

1

5

3 e t + 6 e 2t

= 2 e t

s 3 + 5 s = 3 + 5s =

1

6 e 2 t = 2 − e t − s 3 + 5 s =

s(s 2 + 5) =

1

e t − s 3 + 5 s = 1 s ( s 2 + 5)

1 5 · 1 s 1 s 2

5

s

+ 5 = 1 5 1 5 cos 5t

169

Exercises 4.2

26. (s 2 + 4)(s + 2) =

Exercises 4.2 26. ( s 2 + 4)( s + 2) = s 4 · s

s

Exercises 4.2 26. ( s 2 + 4)( s + 2) = s 4 · s

4 · s 2 + 4 + 4 · s 2 + 4 4 ·

1

s

1

2

1

s

+ 2 = 1 4 cos 2t + 1 4 sin 2t 1 4 e 2t

1

27. (s 2 + s)(